Kerja Sama Sister Province Pemerintah Jawa Barat Dan Prefektur Shizuoka Dalam Mitigasi Bencana Alam Gempa Bumi - Rahayuni Imelda; Sintia Catur Sutantri (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Indonesia is geographically located in the Ring of Fire, which has the potential to cause major earthquakes and tsunamis. One of the areas that is prone to earthquakes is West Java Province, which is known to have quite a number of volcanoes and active faults such as the Lembang fault and the Cimandiri-Baribis fault. The condition of buildings that were damaged or collapsed due to earthquakes was caused by a lack of knowledge regarding building infrastructure that did not comply with Indonesian National Standards and the selection of inappropriate land locations. The lack of education, the absence of earthquake simulation training, and an inadequate early warning system were weaknesses of the government in handling earthquake disasters. To overcome this, the West Java government has established a sister province partnership with the Shizuoka Prefecture government in Japan, which has policies that are said to be successful in reducing earthquake risk. The partnership began in 2017 in the economic sector and human resource capacity building, and was renewed in 2022 with the addition of the disaster management sector. In conducting this qualitative research, interviews were conducted with sources from the West Java Provincial Government and Regional Autonomy Bureau. From the information obtained, the program that was developed was a training or online training course conducted by the Shizuoka Earthquake Prevention Center for the West Java Provincial Disaster Management Agency. This training covered material related to information on past earthquakes and tsunamis, earthquake disaster mitigation, including earthquake simulations conducted on Shizuoka residents. According to the informant, the results of this collaboration will continue to be evaluated for future work programs. Keywords: Earthquake; sister province cooperation; paradiplomacy Abstrak Indonesia secara geografis berada di kawasan Ring of Fire yang berpotensi menjadi ancaman terjadinya gempa dan tsunami besar. Salah satu wilayah yang sering terjadi gempa adalah Provinsi Jawa Barat, yang diketahui memiliki cukup banyak gunung api dan juga sesar-sesar yang masih aktif seperti sesar Lembang dan sesar Cimandiri-Baribis. Kondisi bangunan yang rusak hingga mengalami keruntuhan akibat gempa disebabkan karena minimnya pengetahuan terkait infrastruktur bangunan yang tidak sesuai Standar Nasional Indonesia dan pemilihan lokasi tanah yang kurang tepat. Kurangnya penyuluhan, pelatihan simulasi gempa yang belum ada, hingga sistem peringatan dini yang kurang memadai menjadi kelemahan pemerintah dalam penanganan bencana gempa. Untuk mengatasi hal tersebut, pemerintah Jawa Barat melakukan kerja sama sister province dengan pemerintah Prefektur Shizuoka, Jepang yang memiliki kebijakan yang dikatakan berhasil dalam pengurangan risiko gempa bumi. Kerja sama dilakukan sejak tahun 2017 pada sektor ekonomi dan peningkatan kapasitas Sumber Daya Manusia, kemudian diperbarui pada tahun 2022 dengan penambahan bidang kebencanaan. Dalam menyusun penelitian dengan metode kualitatif ini, dilakukan wawancara dengan narasumber dari Biro Pemerintahan dan Otonomi Daerah Provinsi Jawa Barat. Dari informasi yang didapatkan, program yang dihasilkan adalah adanya pelatihan atau online training course yang dilakukan oleh Pusat Pencegahan Gempa Shizuoka kepada Badan Penanggulangan Bencana Daerah Provinsi Jawa Barat. Pelatihan yang diterima ini berisi penyampaian materi terkait informasi gempa dan tsunami yang pernah terjadi, mitigasi bencana gempa, termasuk simulasi gempa yang dilakukan kepada warga Shizuoka. Menurut narasumber, hasil dari kerja sama ini akan terus dievaluasi untuk jadi program kerja ke depannya. Kata Kunci: Gempa; kerja sama sister province; paradiplomasi